Preparation and Characterization of a Cerium(IV)-incorporated Manganese Oxide OMS-2. Effect of Cerium(IV) Template on Octahedral Molecular Sieves of Manganese Oxide and Characterization of Manganese Oxide Molecular Sieves with Cerium(IV) as Dopant - Evroula Hapeshi; Charis R. Theocharis (Adsorption Science & Technology)
The manganese oxide material K-OMS-2 was synthesized both via a redox reaction between potassium permanganate and manganese nitrate in an acidic medium (nitric acid) under reflux conditions and by the sol–gel reaction between KMnO 4 and maleic acid employed in a 3:1 molar ratio. Cerium(IV) was then added by an ion-exchange method. The structures, morphologies, chemical compositions and thermal stabilities of the resulting materials were studied by X-ray diffraction (XRD), N 2 adsorption/desorption, scanning electron microscopy (SEM), Fourier-transform infrared (FT-IR) spectroscopy, differential scanning calorimetry (DSC) and TGA techniques. Both the morphologies and the surface properties of the materials synthesized by these two methods were different. Thus, the material prepared via the sol–gel process possessed a higher surface area and exhibited both a different type of adsorption isotherm and smaller crystallite sizes than the material synthesized by redox reaction under reflux conditions. The physical and chemical properties of the Ce–K-OMS-2 materials were similar to those of pure cryptomelane. TGA and XRD studies showed that the K-OMS-2 and Ce–K-OMS-2 materials exhibited a greater thermal stability in O 2 rather than N 2 atmospheres. In fact, the Ce(IV) derivatives were more stable thermally than the pure material. For Ce–K-OMS-2 R , the data obtained showed that part of the manganese in the framework was substituted by Ce(IV) ions. In contrast, the data for Ce–K-OMS-2 S indicated that not only did Ce(IV) ions substitute part of the manganese in the framework but that Ce(IV) ions also replaced the K + ions in the tunnel structure of the material.